Association between parental restriction, control and reward on limiting children to eat unhealthy foodsin Kota Kinabalu, Sabah - Liew, Constance Sat Lin; Symeon Mandrinos; Chandrika Murugaiah; Alvin Oliver Payus; Ng, ChiakYot; Khor, Foo Kiang; May, Zaw Soe; Ehab Helmy Abdel Malek Fahmy; ABM Tofazzal Hossain; Rhanye Mac Guad; Aye Aye Wynn; Segaran Ramodran; et al. (Malaysian Journal of Medicine and Health Sciences, 2020)
This study aimed to investigate the relationships between parental effort to control the child’s food intake among primary school children with parents’ ‘control’, ‘restriction’ and ‘reward’ on limiting children to eat unhealthy foods. Methods: Data were collected among 485 primary school children and their parents. Questionnaire for Obesity survey among primary school children was used to document on the child’s daily food intake for one week. Results: All predictor variables are significant at the p<0.05 level. The regression parameter for parents’ effort to restrict the next meal if child eats more than usual, is associated with 0.68631 increase in the parents’ effort to control the child’s food. Similarly, the regression parameter for parents’ effort to restrict the next meal if child eats more than usual is associated with 1.11653 increase in the parents’ effort to control the child’s food intake. Likewise, healthy food as a reward for bad behaviour is associated with 0.37709 increase in the parents’ effort to control the child’s food intake. Conclusion: This research showed that parental effort to control the child’s food intake with the purpose of limiting unhealthy food when the level of parents’ education varies is explained by three predictors (con¬trol, restriction, reward) that are interpreted as the effects in long term. Clinicians, nutritionists and researchers should pay attention to improve parental practices in the communities.